Peningkatan kompetensi pengasuh lansia di Panti Werdha Aisyiyah Sumber Surakarta - Sugiharto, Sugiharto; Kartinah, Kartinah; Kristinawati, Beti; Sulastri, Sulastri; Oktaviana, Wita; Fauzi, Ekan (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: The elderly population in every country around the world is growing, both in number and proportion. It is estimated that by 2030, 1 in 6 people worldwide will be 60 years of age or older. Elderly people living in nursing homes require increased care. Therefore, caregivers in nursing homes must also possess competent knowledge and skills. This can be achieved through structured upgrading of caregivers. Purpose: To provide knowledge and skills to caregivers as an effort to improve their competence in providing elderly care. Method: This community service activity was conducted from May to August 2025 with 12 meetings every Thursday from 8:00 to 11:00 a.m. in the hall of the Aisyiyah Sumber Surakarta Nursing Home. This activity was attended by 18 nursing home managers, both administrative and caregivers. This community service activity was conducted by six lecturers as speakers, facilitated by 10 students. Using LCDs, PowerPoint presentations, and the e-KMS link (https://lansia.giescare.com), participants were educated through lectures, interactive participatory discussions, and demonstrations. The education provided includes basic concepts of the elderly, ICOPE and SKILAS, psychosocial examinations, functional examinations of the elderly, hypertension, diabetes mellitus, rheumatoid arthritis, urinary problems in the elderly, reproductive health in the elderly, psychosocial health in the elderly, emergencies in the elderly, and complementary therapy. Results: The activity went well and received a positive response from the participants. Participants were able to practice simulations with demonstrations of caregiving practices according to the educational instructions. There was a significant increase in the knowledge and skills of elderly caregivers, with an average knowledge score of 30% increasing from the pre-test (average score of 20) to an average score of 60 at the post-test. Caregivers' skills in communication, mobility, self-care, and identifying signs of health risks in the elderly improved. Conclusion: Improving the competence of elderly caregivers through education and training has proven effective in enhancing their knowledge and skills in providing quality healthcare. Systematically designed, comprehensive, interactive, and needs-based training can have a positive impact on the knowledge, skills, and attitudes of elderly caregivers. Suggestion: The implication of this community service program is the importance of continuous learning for elderly caregivers to stay up-to-date with developments in science and technology so they can provide comprehensive, standardized, and increasingly better services. Keywords: Elderly; Elderly caregiver; Integrated care for the elderly; Nursing home Pendahuluan: Populasi lansia di setiap negara di dunia mengalami pertumbuhan, baik dalam jumlah maupun proporsinya. Diperkirakan pada tahun 2030, 1 dari 6 orang di dunia akan berusia 60 tahun ke atas. Lansia yang tinggal di panti memerlukan perhatian lebih. Oleh karena itu para pengasuh lansia di panti juga harus memiliki pengetahuan dan keterampilan yang kompeten. Hal tersebut dapat diperoleh dengan melakukan upgrading bagi pengasuh lansia di panti secara terstruktur. Tujuan: Memberikan pengetahuan dan ketrampilan pada pengasuh lansia sebagai upaya peningkatan kompetensi dalam melakukan perawatan lansia. Metode: Kegiatan pengabdian ini dilaksanakan pada bulan Mei – Agustus 2025 dengan 12 kali pertemuan setiap hari Kamis pukul 08.00 sampai dengan 11.00 di aula Panti Werdha Aisyiyah Sumber Surakarta. Kegiatan ini diikuti oleh 18 pengelola panti baik administrasi maupun pengasuh. Pengabdian kepada masyarakat ini dilakukan oleh 6 dosen sebagai pemateri difasilitasi oleh 10 mahasiswa. Dengan media LCD, PPT, dan link e-KMS (https://lansia.giescare.com), para peserta diberikan edukasi dengan metode ceramah, diskusi interaktif partisipatif, dan demonstrasi. Edukasi yang diberikan meliputi tentang konsep dasar lansia, ICOPE dan SKILAS, pemeriksaan psikososial, pemeriksaan fungsional lansia, hipertensi, diabetes mellitus, rematoid artritis, masalah perkemihan pada lansia, kesehatan reproduksi lansia, kesehatan psikososial pada lansia, kegawatdaruratan pada lansia, dan terapi komplementer. Hasil: Kegiatan berjalan dengan baik dan mendapat respon positif dari para peserta. Para peserta dapat melakukan praktik simulasi dengan demonstrasi penerapan pengasuhan sesuai petunjuk dalam kegiatan edukasi. Terjadi peningkatan yang signifikan terhadap pengetahuan dan keterampilan para pengasuh lansia, dengan peningkatan skor tingkat pengetahuan rata-rata 30% dari pre-test (rata-rata nilai 20) menjadi rata-rata 60 pada saat post-test. Ada peningkatan keterampilan pengasuh dalam berkomunikasi, mobilisasi, perawatan diri, dan identifikasi tanda-tanda risiko kesehatan pada lansia. Simpulan: Peningkatan kompetensi bagi para pengasuh lansia dengan pemberian pendidikan dan pelatihan terbukti efektif dalam meningkatkan pengetahuan dan keterampilan pengasuh lansia dalam pemberian pelayanan kesehatan yang bermutu. Pelatihan yang dirancang secara sistematis, komprehensif, interaktif, dan berdasarkan kebutuhan dapat memberikan dampak positif baik pada tingkat pengetahuan, keterampilan, maupun sikap para pengasuh lansia. Saran: Implikasi dari program pengabdian kepada masyarakat ini adalah pentingnya pembelajaran berkesinambungan bagi pengasuh lansia untuk tetap up-to-date dengan perkembangan ilmu dan pengetahuan sehingga dapat memberikan pelayanan yang komprehensif, sesuai standar dan semakin menjadi lebih baik.